Changing Profile of Rural Marketing Emerging Dimensions of Rural Consumers Behaviour - Kumar, C Rajendra; S Kaptan, Sanjay (Ushus Journal of Business Management, 2021)
Corporate strategies especially Development IT & Satellite communications have opened up new avenues into the rural market. The rural consumer has woken up to existence of multiple brands. What are the implication of this? What are the hurdles in building brand loyalty among the rural consumers? Is rural market the next big thing?